Incorporation of anti-inflammatory agent into calcium hydroxide pulp capping material: An in vitro study of physical and mechanical properties - Louwakul,P. (Japanese Society for Dental Materials and Devices, 2015)
The aims of this study were to investigate the release of fuocinolone acetonide from an experimental pulp capping material containing fuocinolone acetonide (PCFA) and compare some physical and mechanical properties with Dycal ®. The PCFA is a hard-setting calcium hydroxide cement composed of 50 mmol/L fuocinolone acetonide. Conditioned media from the setting material was collected for determination of fuocinolone acetonide release by high performance liquid chromatography and pH measurement by pH meter. The setting time, compressive strength, disintegration, and acid soluble arsenic content were measured according to ISO 3107:2004. Dycal ® was used as control. Fluocinolone aceton ide could release at a range of suitable concentrations from PCFA. The pH, setting time, and acid soluble arsenic content of PCFA were significantly higher than those of Dycal ®. The compressive strength and disintegration of PCFA were comparable to control. PCFA may be considered as an alternative in pulp capping of inflamed dental pulp tissue.